1997
DOI: 10.1103/physrevd.55.733
|View full text |Cite
|
Sign up to set email alerts
|

Collective scattering of massive stars in higher order gravity

Abstract: In the weak field approximation of higher order gravity theory a gravitational potential is described by a Newtonian plus a Yukawa-like term. This new term is used to explain some aspects of galactic dynamics, without considering dark matter. Its presence modifies the scattering probability of a massive intruder star and relaxation time of the stellar system. ͓S0556-2821͑97͒05802-5͔ PACS number͑s͒: 04.50.ϩh, 95.35.ϩd

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…The idea of modified gravity has been re-emerging with various justifications, see for example Refs. [25][26][27][28][29]. The MOND is also studied for the Milky Way and has found that inner Milky Way is completely dominated by baryon matter, which is in agreement with the predictions of standard cold dark matter (CDM) cosmology [30].…”
Section: Overview and Motivationsupporting
confidence: 72%
“…The idea of modified gravity has been re-emerging with various justifications, see for example Refs. [25][26][27][28][29]. The MOND is also studied for the Milky Way and has found that inner Milky Way is completely dominated by baryon matter, which is in agreement with the predictions of standard cold dark matter (CDM) cosmology [30].…”
Section: Overview and Motivationsupporting
confidence: 72%
“…The traditional meson-exchange model [1][2][3][4] describes the NN scattering data quantitatively very well, where the effective degrees of freedom are nucleons and mesons. The intermediate-and long-range parts of the NN interaction are attributed to two-pionexchange, usually parameterized in terms of a σ meson, and one-pion-exchange (OPE).…”
Section: Introductionmentioning
confidence: 99%
“…A possible extension to our current calculation is to consider Ref. [29] where a meson-baryon interaction is derived in the context of the Fock-Tani formalism and obtain a σ πN cross-section from quark physics. The influence of the internal quark structure to the ∆ ressonance can also be addressed and is straightforward.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most successful models in this regime is the UrQMD [31]. From our present approach, general baryon-baryon cross-sections can be calculated, from [19] mesonmeson cross-sections are obtained and from [29] all meson-baryon cross-sections, that appear in UrQMD, can be derived incorporating quark interchange.…”
Section: Discussionmentioning
confidence: 99%